2022
DOI: 10.1038/s41564-022-01107-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal multi-omics analyses link gut microbiome dysbiosis with recurrent urinary tract infections in women

Abstract: Recurrent urinary tract infections (rUTIs) are a major health burden worldwide, with history of infection being a significant risk factor. While the gut is a known reservoir for uropathogenic bacteria, the role of the microbiota in rUTI remains unclear. We conducted a year-long study of women with (n=15) and without (n=16) history of rUTIs, from whom we collected urine, blood and monthly fecal samples for metagenomic and transcriptomic interrogation. During the study, 24 UTIs were reported, and additional samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 65 publications
7
61
1
Order By: Relevance
“…32 In this vein, the activity of fabimycin against UTIs is very promising, given how antibiotic treatment of UTIs is known to trigger Clostridioides diff icile infection 49 and the recently described "gut−bladder axis" in recurrent UTIs. 50,51 Similar to fusidic acid and some other antibiotics, 52,53 the advancement of this class of FabI inhibitors has been complicated by the uniquely poor stability of these compounds in mouse plasma. Given the promising activity of fabimycin in mouse infection models and encouraging data that fabimycin is dramatically more stable in rat and human plasma, it is reasonable to believe that fabimycin efficacy may improve as it is used to treat infections in higher organisms.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In this vein, the activity of fabimycin against UTIs is very promising, given how antibiotic treatment of UTIs is known to trigger Clostridioides diff icile infection 49 and the recently described "gut−bladder axis" in recurrent UTIs. 50,51 Similar to fusidic acid and some other antibiotics, 52,53 the advancement of this class of FabI inhibitors has been complicated by the uniquely poor stability of these compounds in mouse plasma. Given the promising activity of fabimycin in mouse infection models and encouraging data that fabimycin is dramatically more stable in rat and human plasma, it is reasonable to believe that fabimycin efficacy may improve as it is used to treat infections in higher organisms.…”
Section: ■ Discussionmentioning
confidence: 99%
“…While this includes some pathogenic bacteria, such as P. aeruginosa , it also includes many commensal bacteria, suggesting that a suitable FabI inhibitor could be less damaging to the gut microbiome than the typical broad-spectrum antibiotic . In this vein, the activity of fabimycin against UTIs is very promising, given how antibiotic treatment of UTIs is known to trigger Clostridioides difficile infection and the recently described “gut–bladder axis” in recurrent UTIs. , …”
Section: Discussionmentioning
confidence: 99%
“…Though few studies have investigated the relationships between gut and bladder, recent studies have indicated a “gut–bladder axis” linking those two distal organs [ 19 , 20 ], where gut microbiota may play a pivotal role. With the emergence of accumulative evidence, gut microbiome has been reported to be associated with cancer occurrence and development; however, the spectrum of direct and indirect interactions between the gut microbiota and the bladder cancer remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study investigated the polymicrobial nature of recurrent urinary tract infections (rUTIs) and found that E. coli populations in the gut and the bladder were comparable between women with and without a history of rUTI in both relative abundance and phylogroup [37]. However, a deeper lineage level analysis, such as the one performed here, combined with screening of genetic determinants of persistent bladder colonisation from the metagenome assemblies could provide a more refined characterisation of the possible population differences between gut and the bladder.…”
Section: Discussionmentioning
confidence: 99%